(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article reveals the methodological foundations of teaching students to solve differential equations, which contribute to overcoming the difficulties that arise when determining the type of a differential equation and when compiling a differential equation of the process presented in the condition of the problem